2000
DOI: 10.1007/s002210000487
|View full text |Cite
|
Sign up to set email alerts
|

Movement-related potentials are task or end-effector dependent: evidence from a multifinger experiment

Abstract: In a number of recent studies, the specific sensitivity of movement-related EEG potentials toward experimental manipulations of motor tasks using the index finger as a primary end-effector is well documented. The major question in this study was whether different movement-related EEG components are primarily end-effector or task dependent. Accordingly, the experimental task (i.e., the rate of force development - a ratio of peak force to time-to-peak force) was systematically manipulated and the effects of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…This component is readily observed during a force generation task (Slobounov et al 2002) with a higher rate of force production corresponding with increased negativity and an EEG time series comparable to those observed in the present study. de Bruijn et al (2003) also observed a force production negativity after response onset in differing conditions, which led to their conducting separate analyses for the high and low force ranges to separate out the potential contributions from a MMP.…”
Section: Do the Waveforms Reflect Ern Activity?supporting
confidence: 85%
See 2 more Smart Citations
“…This component is readily observed during a force generation task (Slobounov et al 2002) with a higher rate of force production corresponding with increased negativity and an EEG time series comparable to those observed in the present study. de Bruijn et al (2003) also observed a force production negativity after response onset in differing conditions, which led to their conducting separate analyses for the high and low force ranges to separate out the potential contributions from a MMP.…”
Section: Do the Waveforms Reflect Ern Activity?supporting
confidence: 85%
“…One possibility would be movement-monitoring potentials (MMPs) (Chiang et al 2004;Grunewald-Zuberbier and Grunewald 1978;Slobounov et al 1998Slobounov et al , 2000Slobounov et al , 2002, which are slow-moving negative potentials associated with preparation and execution of an action. The time course of this potential spans several seconds, with a rising negativity ϳ1,500 ms before movement onset, and a much larger ERP amplitude than the ERN that can persist for well over 1,000 ms (cf.…”
Section: Do the Waveforms Reflect Ern Activity?mentioning
confidence: 99%
See 1 more Smart Citation
“…This component comprises the peak of the motor potential associated with movement execution and presumably reflects activity in M1 (Toma et al, 2002). M1 is of particular interest as there is strong evidence for its involvement in encoding force as well as movement kinematics (Kakei et al, 1999;Cramer et al, 2002;Slobounov et al, 2002), both relevant aspects in our ballistic power grip task. The observed pattern of an initial amplitude increase with subsequent decrease is particularly interesting as neural activity has been reported to generally decrease in M1 after movement repetition.…”
Section: Discussionmentioning
confidence: 99%
“…description of neural pathways) goes beyond the purpose of the present paper, we need to mention that the primary motor cortex (BA 4) also plays a primary role in the delivery of the motor command to the muscles, thus allowing a refined optimization of joint angles and the subtle tuning of torques [3], [18]. Electrically, a correlate is observed in the beta frequency band (18)(19)(20)(21)(22)(23)(24)(25), where some power decrease is found. Movement completion ends up in a sudden power increase in the beta band, also called event related synchronization (ERS) or beta rebound [12].…”
Section: Introductionmentioning
confidence: 96%